Age Determination from of Ossification Center Fusion around Knee Joint in Mumbai Region: A Radiological Study - Bhise, S S; Chikhalkar, B G; Nanandkar, S D; Chavan, G S; Rayamane , Anand P (Journal of Indian Academy of Forensic Medicine, 2015)
The bones of human skeletons develop from separate ossification centers. From these centers ossification progresses till the bone is completely formed. These changes can be studied by means of X rays and these changes are age related. It is therefore possible to determine the approximate age of an individual by radiological examination of bones till ossification is complete. This radiological study was carried out with the objective to assess the general skeletal maturity around knee joint, of subjects in Mumbai region. 170 males between age group of 3-25 years and 66 females between age group of 3-23 years attending the outpatient department of this hospital were selected. Age confirmed from history and noting the birth dates from driving license, passport, rations card or voter‟s card. The cases were selected after ruling out the nutritional, developmental, and endocrinal abnormality which affects the skeletal growth. Data analysis was done in P4 computer using HPSS software. At the end conclusions were drawn which are compared with available results of various previous studies.